miR-371b-5p-Engineered Exosomes Enhances Tumor Inhibitory Effect - Xue, Qiang; Yang, Yang; Yang, Linlin; Yan, Xiaodi; Shen, Zihao; Liu, Jiajia; Xue, Jianhua; Zhao, Wei; Liu, Xianchen (Frontiers in Cell and Developmental Biology, 2021)
Background: Exosomes are well-known natural nanovesicles, that represent one of the recently discovered modes of intercellular communication due to their ability to transmit cellular components. Exosomes have been reported to have potential as natural vectors for carrying functional small RNAs and delivering chemotherapeutic agents to diseased cells. In this study, we aimed to investigate the role of exosomes in carrying miRNA for targeting tumor cells. Methods: We present a novel method for engineering exosomes with functional miR-317b-5b to target tumor cells. MiR-317b-5b exerts its anti-tumor function via its expression in tumors. RT-qPCR was performed to assess the levels of miR-371b-5p, FUT-4. Western blot was performed to measure the levels of CD9, CD81, FUT-4 proteins. Confocal microscopy was used to observe the internalization of miR-317b-5b in tumor cells. CCK-8, EdU, flow cytometry, wound-healing migration and transwell assays were performed to evaluate cell viability, proliferation, migration and invasion, respectively. Results: Our findings illustrated that miR-317b-5b-loaded engineered exosomes were internalized by tumor cells. MiR-317b-5b was overexpressed in tumor cells treated with miR-317b-5b-loaded engineered exosomes. The internalization of miR-317b-5b in tumor cells was accompanied by changes of cell viability, proliferation, apoptosis, and migratory and invasive capability. We found that miR-317b-5b-loaded engineered exosomes were presence in tumor tissue sections and miR-317b-5b was overexpressed in tumor tissues of osteosarcoma tumor-bearing mice infected with miR-317b-5b-loaded engineered exosomes. MiR-317b-5b-loaded engineered exosomes had the anti-tumor efficiency in vivo. Conclusion: Our findings show that miR-317b-5b-loaded engineered exosomes can be used as nanocarriers to deliver drug molecules such as miR-317b-5b both in vitro and in vivo to exert its anti-tumor functions.